Predictors of Vaginal Delivery among Patients Admitted with Severe Preeclampsia - Myers, Sabrena; Pyne, Abigail; Darling, Alice; Al-Shibli, Noor; Cate, Jennifer J.M.; Grace, Matthew R.; Wheeler, Sarahn; Dotters-Katz, Sarah K. (American Journal of Perinatology, 2024)
Objective This study aimed to assess the rates of vaginal delivery (VD) and the predictors of VD in a cohort of patients with early (<34 weeks) preeclampsia with severe features (Early Severe PreEClampsia [ESPEC]).Study Design We conducted a retrospective cohort study of patients with ESPEC admitted to a single center from 2013 to 2019. Exclusion criteria included patients with contraindications to labor, multifetal gestation, or presenting in spontaneous labor. Patient characteristics were abstracted. The primary outcome was rate of VD. Secondary outcome was factors associated with VD. Secondary analysis performed including only primiparous patients. Bivariate statistics and logistic regression were used to analyze data.Results Of 229 patients with ESPEC, 184 (80%) were candidates for labor. Of those, 74 (40%) underwent prelabor cesarean delivery (CD). Among the 110 remaining patients who attempted VD, 47 (43%) were successful. No significant differences in characteristics between VD and CD patients were found on bivariate analysis. In regression models, BMI ≥ 40 was associated with increased odds of CD (adjusted odds ratio [aOR]: 2.83, 95% confidence interval [CI]: 1.01, 7.95), whereas private insurance was associated with reduced odds of CD (aOR: 0.37, 95% CI: 0.16, 0.86). In planned secondary analysis of primiparous patients, 101/123 (82%) were candidates for labor. Of those, 29 underwent prelabor CD. The VD rate among primiparous patients attempting labor was 40% (29/72). In this subgroup, private insurance was associated with VD (71 vs. 46%, p = 0.03). In regression models, only private insurance remained associated with CD (aOR: 0.30, 95% CI: 0.10, 0.92).Conclusion Patients with ESPEC who attempted VD were successful less than half of the time, with similar rates among the subset of primiparous patients. BMI ≥ 40 was associated with increased odds of CD, whereas private insurance was associated with reduced odds of CD. These data may aid providers in counseling patients with ESPEC on the likelihood of successful VD.Key Points
Keywords: preeclampsia; preterm vaginal delivery; early preeclampsia with severe features; obesity; cesarean delivery; predictors